2017
DOI: 10.1111/obr.12545
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic minority enrollment in randomized clinical trials of behavioural weight loss utilizing technology: a systematic review

Abstract: Many racial and ethnic minority groups (minorities) are disproportionately affected by overweight and obesity; however, minorities are often under-represented in clinical trials of behavioural weight loss (BWL) treatment, potentially limiting the generalizability of these trials' conclusions. Interventions involving technology may be particularly well suited to overcoming the barriers to minority enrollment in BWL trials, such as demanding or unpredictable work schedules, caregiving responsibilities and travel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 102 publications
2
34
0
Order By: Relevance
“…With the rapid evolution of digital health devices and platforms, offering choices between modalities likely enhances convenience and flexibility and has been shown to promote engagement (90). Further, recent years have seen changing preferences toward accessing the Internet via a smartphone rather than a personal computer, particularly among Hispanic and Black adults, individuals residing in rural areas, and lower‐income populations (91)—groups who all have heightened obesity risk (15,92) and yet are traditionally underrepresented in obesity treatment (93). To address these changing attitudes and broaden the reach of behavioral obesity treatment, interventionists should leverage mobile platforms for self‐monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid evolution of digital health devices and platforms, offering choices between modalities likely enhances convenience and flexibility and has been shown to promote engagement (90). Further, recent years have seen changing preferences toward accessing the Internet via a smartphone rather than a personal computer, particularly among Hispanic and Black adults, individuals residing in rural areas, and lower‐income populations (91)—groups who all have heightened obesity risk (15,92) and yet are traditionally underrepresented in obesity treatment (93). To address these changing attitudes and broaden the reach of behavioral obesity treatment, interventionists should leverage mobile platforms for self‐monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the use of technology to both recruit and deliver behavioral weight loss interventions shows promise for increasing inclusion of diverse samples. A recent review found that weight loss trials that incorporated smartphone use had greater enrollment of racial/ethnic minority participants than trials that did not incorporate smartphones ( Rosenbaum et al, 2017 ). Emerging studies are revealing that interventions delivered via online programs ( Sepah et al, 2015 ) and online social networks are effective at producing weight loss in the absence of clinic visits ( Pagoto et al, 2015 ; Turner-McGrievy and Tate, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, most areas of research have groups that are underrepresented. Within the area of behavioral weight control, samples are predominately female [2][3][4][5] and non-Hispanic White [5,6].…”
Section: Introductionmentioning
confidence: 99%